Incomplete Kawasaki Disease with Peripheral Facial Nerve Palsy and Lung Nodules: A Case Report and Literature Review - Marco Maglione; Annalisa Barlabà; Michela Grieco; Rosaria Cosimi; Giangiacomo Di Nardo; Giovanni Maria Di Marco; Monica Gelzo; Giuseppe Castaldo; Celeste Tucci; Raffaella Margherita Iodice; Maria Concetta Lonardo; Vincenzo Tipo; et al. (MDPI AG, 2023)
The diagnosis of Kawasaki disease (KD) is challenging and often delayed mainly in case of young infants and in presence of an incomplete disease and atypical features. Facial nerve palsy is one of the rare neurologic symptoms of KD, associated with a higher incidence of coronary arteries lesions and may be an indicator of a more severe disease. Here, we describe a case of lower motor neuron facial nerve palsy complicating KD and perform an extensive literature review to better characterize clinical features and treatment of patients with KD-associated facial nerve palsy. The patient was diagnosed at the sixth day of disease and presented extensive coronary artery lesions. A prompt treatment with intravenous immunoglobulins, aspirin and steroids obtained a good clinical and laboratory response, with resolution of facial nerve palsy and improvement of coronary lesions. The incidence of facial nerve palsy is 0.9-1.3%; it is often unilateral, transient, more frequent on the left and seemingly associated with coronary impairment. Our literature review showed coronary artery involvement in the majority of reported cases (27/35, 77%) of KD with facial nerve palsy. Unexplained facial nerve palsy in young children with a prolonged febrile illness should prompt consideration of echocardiography to exclude KD and start the appropriate treatment.